RNA sequencing indicates widespread conservation of circadian clocks in marine zooplankton. Issue 1 (31st January 2023) - Raghavan, Venket; Eichele, Gregor; Larink, Otto; Karin, Eli Levy; Söding, Johannes
Abstract: Zooplankton are important eukaryotic constituents of marine ecosystems characterized by limited motility in the water. These metazoans predominantly occupy intermediate trophic levels and energetically link primary producers to higher trophic levels. Through processes including diel vertical migration (DVM) and production of sinking pellets they also contribute to the biological carbon pump which regulates atmospheric CO2 levels. Despite their prominent role in marine ecosystems, and perhaps, because of their staggering diversity, much remains to be discovered about zooplankton biology. In particular, the circadian clock, which is known to affect important processes such as DVM has been characterized only in a handful of zooplankton species. We present annotated de novo assembled transcriptomes from a diverse, representative cohort of 17 marine zooplankton representing six phyla and eight classes. These transcriptomes represent the first sequencing data for a number of these species. Subsequently, using translated proteomes derived from this data, we demonstrate in silico the presence of orthologs to most core circadian clock proteins from model metazoans in all sequenced species. Our findings, bolstered by sequence searches against publicly available data, indicate that the molecular machinery underpinning endogenous circadian clocks is widespread and potentially well conserved across marine zooplankton taxa.